Холевина Eocatops pelopis (Coleoptera, Leiodidae, Cholevinae) на юге Восточной Европы и ее прохорез на север в голоцене - Перковский, Е.Э.; Гонтаренко, А.В. (Вестник зоологии, 2002)
Впервые изучены признаки популяций Eocatops pelopis (Reitter) с северо-востока континентальной части ареала (Одесская, Херсонская, Ростовская обл. и Крым). Populations of the cholevine Eocatops pelopis (Reitter) from the extreme north-east of its continental distribution range (Odessa, Kherson, Rostov regions and Crimea) are studied for the first time. Variability of such stable in the other congeners characters, as the form of elytral apex and the structure of antennae, was demonstrated; specimens, indistinguishable in these characters from those described from Lapland as a distinct species (Szymczakowski, 1975), were found. The latter form is reconsider as a subspecies of E. pelopis. All records of Eocatops from Ukraine and European part of Russia assigned to E. pelopis. Appearance of E. “lapponicus” in Lapland might not take place before Holocene optimum; the most parsimonious explanation of this event suggests transition of one of the East European populations of E. pelopis to commensalism on Formica lemani Bondroit in Holocene, with the subsequent prochoresis to the North together with the host population. This hypothesis well explains limited range of E. pelopis in Sweden and Finland.